Employees’ Motivation in Public and Private Commercial Banks in Bangladesh: A Study on Need-Based Approach - Rahman , Md. Hasebur (Global Disclosure of Economics and Business, 2013)
Motivation remains a key secrete of managing people at organizational interfaces. Different people from differ background come together within organization having different aims incompatible to organizational aims. Motivation acts as key forces to drive diversified workforce to meet organizational objectives. In Bangladesh Performance of public commercial bank in comparison to the private commercial bank has long been a point of dissuasion. This study has made a comparison between employees of public and private commercial bank in Bangladesh regarding their motivation on the basis of need theories of motivation. Their motivation level was measured and compared on the basis of two major constructs identified from the literature review. These construct are perception about the benefits received from the job, and perception about the job nature and job environment in the banking organization. It is found that employees of private commercial bank scored slightly higher in both the construct however there is no significant differences have been proved about benefit received from the job and perception about job nature and environment. Differences were found between the two groups on the relative perception they placed on existing factors of motivation.JEL Classification Code: G20; G29